Electrohydraulic Lithotripsy of an Impacted Enterolith Causing Acute Afferent Loop Syndrome - Cho, Young Sin (The Korean Society of Gastrointestinal Endoscopy, 2014)
Afferent loop syndrome caused by an impacted enterolith is very rare, and endoscopic removal of the enterolith may be difficult if a stricture is present or the normal anatomy has been altered. Electrohydraulic lithotripsy is commonly used for endoscopic fragmentation of biliary and pancreatic duct stones. A 64-year-old man who had undergone subtotal gastrectomy and gastrojejunostomy presented with acute, severe abdominal pain for a duration of 2 hours. Initially, he was diagnosed with acute pancreatitis because of an elevated amylase level and pain, but was finally diagnosed with acute afferent loop syndrome when an impacted enterolith was identified by computed tomography. We successfully removed the enterolith using direct electrohydraulic lithotripsy conducted using a transparent cap-fitted endoscope without complications. We found that this procedure was therapeutically beneficial.